Changes in plasma amyloid beta in a longitudinal study of aging and Alzheimer's disease. Issue 1 (14th March 2013) - Rembach, Alan; Faux, Noel G.; Watt, Andrew D.; Pertile, Kelly K.; Rumble, Rebecca L.; Trounson, Brett O.; Fowler, Christopher J.; Roberts, Blaine R.; Perez, Keyla A.; Li, Qiao‐Xin; Laws, Simon M.; Taddei, Kevin; et al.
Abstract: Background: A practical biomarker is required to facilitate the preclinical diagnosis of Alzheimer's disease (AD). Methods: Plasma amyloid beta (Aβ)1–40, Aβ1–42, Aβn–40, and Aβn–42 peptides were measured at baseline and after 18 months in 771 participants from the Australian Imaging Biomarkers and Lifestyle (AIBL) study of aging. Aβ peptide levels were compared with clinical pathology, neuroimaging and neuropsychological measurements. Results: Although inflammatory and renal function covariates influenced plasma Aβ levels significantly, a decrease in Aβ1–42 /Aβ1–40 was observed in patients with AD, and was also inversely correlated with neocortical amyloid burden. During the 18 months, plasma Aβ1–42 decreased in subjects with mild cognitive impairment (MCI) and in those transitioning from healthy to MCI. Conclusion: Our findings are consistent with a number of published plasma Aβ studies and, although the prognostic value of individual measures in any given subject is limited, the diagnostic contribution of plasma Aβ may demonstrate utility when combined with a panel of peripheral biomarkers.